-(5+3x)=-(x-3)

Simple and best practice solution for -(5+3x)=-(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5+3x)=-(x-3) equation:


Simplifying
-1(5 + 3x) = -1(x + -3)
(5 * -1 + 3x * -1) = -1(x + -3)
(-5 + -3x) = -1(x + -3)

Reorder the terms:
-5 + -3x = -1(-3 + x)
-5 + -3x = (-3 * -1 + x * -1)
-5 + -3x = (3 + -1x)

Solving
-5 + -3x = 3 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-5 + -3x + x = 3 + -1x + x

Combine like terms: -3x + x = -2x
-5 + -2x = 3 + -1x + x

Combine like terms: -1x + x = 0
-5 + -2x = 3 + 0
-5 + -2x = 3

Add '5' to each side of the equation.
-5 + 5 + -2x = 3 + 5

Combine like terms: -5 + 5 = 0
0 + -2x = 3 + 5
-2x = 3 + 5

Combine like terms: 3 + 5 = 8
-2x = 8

Divide each side by '-2'.
x = -4

Simplifying
x = -4

See similar equations:

| 40+8t=12t-36 | | 3y-6=5y-35 | | -5x+3-(-2x)+10=-3 | | -6-n=-5(8-4n)-4n | | -118=-10(2p-8)+2 | | -3.2+14s=15s | | 14x^2+28x-240=0 | | -3j-4=-22 | | 2m+10=0 | | -2(1+6v)+8=-90 | | 7/9d-7=5/9d-3 | | 19=-4x+5-2 | | sin(5x)=0.5 | | 8x+4(-2x-2)=-4(x+1) | | -6m-8m=12-8m | | 1x^2+8x-325=0 | | 5x^2-3x-14= | | 1.00/2.00(x-6.00)=7.00 | | 1/2(x-6)=7 | | (1/3)*3.14*49=250 | | 42m^2+36m-96=0 | | 1x^2+9x-400=0 | | 6-8i/3i | | 1000/150 | | 5-8(b+1)=-12-5b | | ax+(a-1)=y | | 17p+12=17p-13 | | x-(-8)=5 | | 19x+11=15x+15 | | 56Zz+2=22z | | 1000=2x^2+16x+310 | | (-2/3)/4 |

Equations solver categories